UNVEILING TRENDS: HALAL MEDICINE CHOICES AMONG STUDENTS IN GREATER JAKARTA (JABODETABEK) - Wati, Meilina; Priantina, Anita (Al-Infaq: Jurnal Ekonomi Islam, 2024)
Over the counter and restricted over-the-counter medications are commonly used by students because they are easily accessible and can be purchased when feeling unwell. The aim of this study is to understand the purchasing behaviour of over the counter and restricted over-the-counter medicines labelled as halal among students in the Jabodetabek region. This study examines the influence of the theory of planned behaviour (TPB), which includes behavioural control, subjective norms and attitudes, on the purchasing behaviour of halal labelled medicines. The research results show that behavioural control and subjective norms significantly influence the purchasing behaviour of halal medicines among students in the Jabodetabek region. However, contrary to initial expectations, no significant influence of the attitudinal variable was found on halal medicine purchasing behaviour among students in the Jabodetabek region.